Application of transcutaneous electrical nerve stimulation in monitored anesthesia care during foraminoscopy: a randomized double-blind controlled trial - Sun, Shuhui; Zhang, Lei; Yu, Dongdong; Jiang, Li; Yang, Ge; Zhang, Long; Tian, Yu; Xu, Chunxiao; Zhang, Dong (Frontiers in Medicine, 2025)
BackgroundAs minimally invasive surgical techniques have evolved, foraminoscopy has emerged as a predominant surgical procedure. This technique utilizes the intervertebral foramen as the primary surgical pathway and addresses lumbar intervertebral disk issues through endoscopic intervention. However, since the surgery is performed under local anesthesia, achieving satisfactory anesthesia poses significant challenges. This investigation sought to assess the efficacy and comparative differences between two non-pharmacological analgesic approaches: transcutaneous electrical nerve stimulation (TENS) and trans-auricular vagus nerve stimulation (taVNS), in the context of monitored anesthesia care (MAC) during foraminoscopy.MethodsThis investigation adopted a randomized, double-blind, controlled trial design. The participants were randomly divided into the TENS group and the taVNS group. Each group was further divided into three stimulation modes: continuous wave, intermittent wave, and dense–sparse wave. In each group, electrical stimulation was applied 30 min prior to surgery. The main parameters to be evaluated included the patients’ Visual Analogue Scale (VAS) scores, heart rate variability (HRV), bispectral index (BIS), Modified Observer’s Assessment of Alertness/Sedation Scale (MOAA/S) and the supplemental use of oliceridine fumarate during the surgery.DiscussionThis study explores the effect of non-pharmacological electrical stimulation techniques in MAC during foraminoscopy through a randomized controlled trial. If proven effective, these techniques could provide viable non-pharmacological analgesic alternatives for foraminoscopy procedures. Additionally, by comparing different waveform stimulations, the electrical stimulation parameters can be further optimized.